Effect of varieties and weed-control practices on rice (Oryza sativa) productivity and weed growth - A.K. GOGOI; D.J. RAJKHOWA; R. KANDALI (Indian Journal of Agronomy, 2001)
A field experiment was conducted during rainy season of 1995 and 1996 to evaluate the competitive ability of traditional and high-yielding rice (Oryza sativa L.) varieties and to find out suitable weed-control practices for transplanted rice. Akisali, a tall traditional variety, was found to reduce the weed dry-matter accumulation significantly compared with the other varieties tested. Different weed- control practices significantly reduced dry-matter accumulation of weed and increased the yield of rice over unweeded check in 1 out of 2 years of experimentation. Butachlor +2,4-D (1.0 kg/ha) in 60:40 proportion and Anilofos (0.4 kg/ha) were equally effective in controlling weeds and increasing the yield of rice.
Keywords: Rice; Weed control; Rice productivity; Weed growth